In vitro assessment of potential probiotic lactic acid bacteria isolated from the gastrointestinal tract of chickens - Nokhaiz, K.; Bukhari, S.M.; Rehman, K.U.; Chohan, Hafeez ur Rehman; Shahzad, A.A.; Andleeb, S.; Ali, W. (International Journal of Biology and Chemistry, 2025)
The global prohibition on antibiotics as growth promoters in poultry has prompted a shift toward probiotics as viable substitutes. Lactic acid bacteria (LAB) offer various benefits, including modulation of gut microbiota, maintenance of intestinal equilibrium, and enhancement of immune function. This study isolated and identified Lactobacillus strains from chicken small intestines, evaluating their in vitro survival and gastrointestinal (GI) colonization capabilities. LAB was cultured on de Man Rogosa Sharpe (MRS) agar for 24-48 hours, with species-specific strains identified through biochemical tests and 16S rRNA gene sequencing. Sequence analysis identified the species as Lactobacillus plantarum, Lactobacillus acidophilus, and Lactobacillus casei. Their resilience to simulated gastric conditions and antibiotic susceptibility assessed via the agar well diffusion method, indicated robust tolerance to pH 3.5 and 0.3% bile salts, alongside notable resistance (90%) to tetracycline. Growth kinetics at varying temperatures and NaCl concentrations revealed optimal conditions at 37°C and 4% NaCl, respectively, with growth diminishing at higher concentrations. In conclusion, Lactobacillus species exhibit significant resilience to harsh GI conditions, underscoring their potential as effective antibiotic alternatives in poultry production. Keywords: antibiotic alternatives, gut microbiota, lactic acid bacteria, microbial ecology, poultry production, gastrointestinal tract